Implementation of the Ta’lim Qur’an Program in Ensuring Students’ Qur’anic Reading Literacy Competence - Majid, Abdul Hakim; Aji, Muhammad Setya; Sholihuddin, Moh; Miftah, Muhammad (Published by the Islamic Religious Education Study Program Faculty of Tarbiyah and Teacher Training Kiai Haji Achmad Siddiq University, Jember, East Java, Indonesia, 2026)
This study investigates the implementation of the Ta’lim Qur’an Program (PTQ) in ensuring students’ Qur’anic reading literacy competence at Sunan Kudus State Islamic University. The research addresses the challenge of uneven Qur’anic reading proficiency among university students and examines how PTQ functions as an institutional quality assurance mechanism in Islamic higher education. Using a qualitative case study design, data were collected through participatory observation, in-depth interviews with program coordinators, tutors (ustaz/ustazah), and students from various faculties, as well as analysis of curriculum and program documents. The findings reveal that PTQ is implemented through a structured, tiered learning system (BTQ, Tartil, Tahfidz, and Tafsir) combined with an andragogical, problem-based approach to Qur’anic instruction. This implementation effectively improves students’ basic Qur’anic reading literacy, particularly in tahsin and tartil, while also strengthening their spiritual discipline and learning motivation. However, the program faces challenges related to limited instructional time, inconsistent student attendance, and supervision constraints. Overall, the study demonstrates that PTQ plays a significant role in ensuring minimum standards of Qur’anic reading competence and provides a practical model for strengthening Qur’anic literacy and quality assurance in Islamic higher education institutions.